Clinical Presentation of Measles at the Pediatric Ward in Dr. Pirngadi Hospital Medan - Mardiana K. Djayusman; Margaretha Damanik; Erijana Malik Miraza; Charles Hutasoit; Chairuddin P. Lubis (Indonesian Pediatric Society, 1992)
A descriptive study was done on 55 infants and children with measles during January 1988- December 1989. They comprised 1.08% of the total sum of 5075 children hospitalized during that period. Measles without any complication was found in 5.4% of the subjects, and bronchopneumonia was the most common complication (75%). The highest prevalence was found in the age group of 1-5 years (72.8%). Most of the cases (98.2%) suffered from mild to severe malnutrition and they had not previously been vaccinated against measles.